FORMATION OF MATHEMATICAL EXPRESSION OF AUTOMATIC CONTROL SYSTEMS IN STUDENTS - Ulukhanov Ibrokhim Tokhtakhojaevich; Tulkinboyev Ixtiyor Toxirjon ugli; Erkinova Sitoraxon Erkinjon kizi (Scholar Express Journal, 2023)
The article focuses on the issues of modernizing the educational system, restructuring it structurally, changing and updating educational programs, taking into account the modern achievements of Education, Science, Technology and technology, economy and Culture on a global scale. In this regard, it is envisaged that the broad adoption of advanced technologies, integration of continuing education with science and production in the development of economic issues, entrepreneurship, small and private business, the introduction of a differentiated approach to education in accordance with the abilities and capabilities of students, the creation of advanced pedagogical technologies of education, modern educational and methodological complexes will be the basis for
Keywords: Educational modernization; value; virtue; environment